Pendampingan Pembuatan Banner, Daftar Menu dan Poster Digital untuk UMKM di Kelurahan Sukajaya Kota Serang - Amalia Nabilah; Ernike Fatih Ataitani; Riana Pratiwi; Suryani Suryani; Tri Windi Oktara; Siti Marfu’ah; Ratu Humaemah (PRAXIS: Jurnal Pengabdian kepada Masyarakat, 2026)
This community service activity aims to assist Micro, Small, and Medium Enterprises (MSMEs) in Sukajaya Sub-District, Serang City, in developing promotional media both offline and online through the WhatsApp platform. The main issue identified is the limited ability of MSME owners to utilize promotional media and design tools to expand their market reach. The implementation methods included field surveys, design execution using Canva, and the distribution of the final promotional materials. The field findings revealed that most MSMEs in Sukajaya Sub-District, Serang City, Banten, did not yet have visual promotional media such as banners or menu lists, resulting in a plain and less informative appearance for new customers. In terms of online promotion, some businesses had used WhatsApp, but only to send product photos without design elements or price information, making their promotions less appealing. Consequently, their promotional activities remained limited and ineffective in attracting new consumers beyond their immediate surroundings.